2003
DOI: 10.1097/00004836-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Possible Protective Effect of 5-Aminosalicylic Acid on Helicobacter pylori Infection in Patients With Inflammatory Bowel Disease

Abstract: Although low, the prevalence of Hp infection in our patients was not significantly different from that in the controls. 5-ASA, and not sulfasalazine, may have a protective effect against Hp infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
2
28
0
4
Order By: Relevance
“…The prevalence of this bacterial infection is lower in CD compared to UC, in the majority of these studies. Potential confounders include the effect of salazopyrine, other 5-ASA compounds, and antibiotics on the carriage and eradication of H pylori [26,27] . However, neither salazopyrine nor the other 5-ASA dr ugs used in IBD reach the concentrations required in the corpus and antrum of the stomach to effect H pylori eradication.…”
Section: H Pylori Exposurementioning
confidence: 99%
“…The prevalence of this bacterial infection is lower in CD compared to UC, in the majority of these studies. Potential confounders include the effect of salazopyrine, other 5-ASA compounds, and antibiotics on the carriage and eradication of H pylori [26,27] . However, neither salazopyrine nor the other 5-ASA dr ugs used in IBD reach the concentrations required in the corpus and antrum of the stomach to effect H pylori eradication.…”
Section: H Pylori Exposurementioning
confidence: 99%
“…Some researchers reported that incidence of H. pylori is lower in UC patients than in healthy populations (9)(10)(11)(12). Possible causes of this low rate of H. pylori in UC patients are the immunopathological characteristics of UC and the medications used in UC, such as 5-aminosalicylic acid (5-ASA) and antibiotics (9)(10)(11)(12). We investigated the incidence of H. pylori in individuals with UC and determined the impact of several characteristics of UC, including extent and severity of UC, on the incidence of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these later studies further substituted H. pylori serum IgG or IgA serology for the C 13 urea breath test, an accurate test for assessing active (as opposed to past) infection. These studies also unequivocally confirmed a lower prevalence of H. pylori in IBD patients [66,67,68]. Although all early studies were conducted on European populations, in which IBDs are much more common than in other geographical areas of the world, several more recent studies have confirmed the same trends in Asian and American populations [69,70,71].…”
Section: Epidemiological Evidence Suggests An Inverse Association Betmentioning
confidence: 74%